Private Health Insurance in OECD Countries The Benefits and Costs for Individuals and Health Systems - Colombo, Francesca (OECD Health Working Papers, 2004)
Governments often look to private health insurance (PHI) as a possible means of addressing some health system challenges. For example, they may consider enhancing its role as an alternative source of health financing and a way to increase system capacity, or promoting it as a tool to further additional health policy goals, such as enhanced individual responsibility. In some countries policy makers regard PHI as a key element of their health coverage systems While private health insurance represents, on average, only a small share of total health funding across the OECD area, it plays a significant role in health financing in some OECD countries and it covers at least 30% of the population in a third of the OECD members. It also plays a variety of roles, ranging from primary coverage for particular population groups to a supporting role for public systems. This paper assesses evidence on the effects of PHI in different national contexts and draws conclusions about its ...